FORAGING BEHAVIOR OF BLACK DRONGO (DICRURUS MACROCERCUS) IN NALGONDA DISTRICT OF ANDHRA PRADESH, INDIA - NARAYANA, B. LAXMI; RAO, V. VASUDEVA; REDDY, V. VENKATESWARA (The Bioscan, 2014)
The present investigation is about foraging behavior of insectivorous bird species Black Drongo (Dicrurus macrocercus) in Nalgonda District of Andhra Pradesh, India. The study was carried out from December 2010 to March 2013. 1114 foraging observations bird used a variety of perch types for hunting the prey; in general the electric power lines was a frequent perch type used 63%, classified in to 3 meter categories up to 12 m height, perching heights (N=1104) principally used 9-12 m and foraging heights (N=466) 6-9 m 48 %. While the use of foraging substrate (N=331) as plants 59% and aerial feeding (N=151) were key feeding technique recorded 52%. In Perch types, perching and foraging heights, foraging substrates and foraging methods based on the above studies, it is recognized that foraging behavior of Black Drongo are mostly interlinked with habitat and accessibility of food resources.